Molecular Mechanisms of Apoptosis Induction and Its Regulation by Fatty Acids in Pancreatic β-Cells - Šrámek, Jan; Němcová-Fürstová, Vlasta; Kovář, Jan (International journal of molecular sciences, 2021)
Pancreatic β-cell failure and death contribute significantly to the pathogenesis of type 2 diabetes. One of the main factors responsible for β-cell dysfunction and subsequent cell death is chronic exposure to increased concentrations of FAs (fatty acids). The effect of FAs seems to depend particularly on the degree of their saturation. Saturated FAs induce apoptosis in pancreatic β-cells, whereas unsaturated FAs are well tolerated and are even capable of inhibiting the pro-apoptotic effect of saturated FAs. Molecular mechanisms of apoptosis induction by saturated FAs in β-cells are not completely elucidated. Saturated FAs induce ER stress, which in turn leads to activation of all ER stress pathways. When ER stress is severe or prolonged, apoptosis is induced. The main mediator seems to be the CHOP transcription factor. Via regulation of expression/activity of pro- and anti-apoptotic Bcl-2 family members, and potentially also through the increase in ROS production, CHOP switches on the mitochondrial pathway of apoptosis induction. ER stress signalling also possibly leads to autophagy signalling, which may activate caspase-8. Saturated FAs activate or inhibit various signalling pathways, i.e., p38 MAPK signalling, ERK signalling, ceramide signalling, Akt signalling and PKCδ signalling. This may lead to the activation of the mitochondrial pathway of apoptosis, as well. Particularly, the inhibition of the pro-survival Akt signalling seems to play an important role. This inhibition may be mediated by multiple pathways (e.g., ER stress signalling, PKCδ and ceramide) and could also consequence in autophagy signalling. Experimental evidence indicates the involvement of certain miRNAs in mechanisms of FA-induced β-cell apoptosis, as well. In the rather rare situations when unsaturated FAs are also shown to be pro-apoptotic, the mechanisms mediating this effect in β-cells seem to be the same as for saturated FAs. To conclude, FA-induced apoptosis rather appears to be preceded by complex cross talks of multiple signalling pathways. Some of these pathways may be regulated by decreased membrane fluidity due to saturated FA incorporation. Few data are available concerning molecular mechanisms mediating the protective effect of unsaturated FAs on the effect of saturated FAs. It seems that the main possible mechanism represents a rather inhibitory intervention into saturated FA-induced pro-apoptotic signalling than activation of some pro-survival signalling pathway(s) or metabolic interference in β-cells. This inhibitory intervention may be due to an increase of membrane fluidity.
Keywords: Animals; Stress, Physiological; biologické modely; apoptóza; mastné kyseliny; caspase; autophagy; Mitochondria; Fatty Acids; Apoptosis; Diabetes Mellitus, Type 2; beta-buňky; lidé; Models, Biological; Lipid Metabolism; Endoplasmic Reticulum; pancreatic β-cell; saturated fatty acid; type 2 diabetes mellitus; kinase; unsaturated fatty acid; signální transdukce; diabetes mellitus 2. typu; Signal Transduction; metabolismus lipidů; fyziologický stres; mitochondrie; fatty acid metabolism; Insulin-Secreting Cells; apoptosis induction; Cell Survival; ER stress; zvířata; viabilita buněk; endoplazmatické retikulum; Humans